Efecto de fuentes de nitrógeno y carbohidratos sobre la digestión in vitro de residuos agrícolas. (1989)
An in vitro digestion study was conducted to evaluate the effect of eight nitrogen (N) compounds, and the interaction with three energy sources on in vitro digestibility of milo stalk, cane bagasse and wheat straw. A total of 523 sampes of the substrates and fluid rumen was tested using urea, NH4H2PO41 (NH4)2So4, NH4CI, NH40H, cotton seed meal (CSM) and soil bean meal (SBM), at doses of 1.0 and 1.5% of added N, supplement with starch at 15%, glucose at 10% or sucrose at 10%. Increase in digestibility (P < 0.05) were observed with energy source plus urea at 1.0 and 1.5%. Digestibility increased by 8.7; 7.2 and 9.4 percentage units (p.u) for milo stalk; 4.0; 4.2 and 6.1 (p.u) for bagasse and 2.3; 4.4 and 4.5 (p.u) for wheat straw with glucose, sucrose or starch, respectively. Differences (P < 0.05) were found with NH4NO3, NH4H2PO41 (NH4)2SO4 at 1.0 or 1.5% with glucose, sucrose or starch, and the ammonium chloride had an effect (P < 0.05), equivalent to 8.5% for milo stalk, 5% for bagasse and 1% for wheat straw plus glucose, sucrose or starch. Ammonium hydroxide reduced digestibility by 5.9% at 1% level. However, it showed an increment of 4.8% when sucrose was added. Reduction of 10.8% as an average was registered at 1.5% level with the three energy sources. On the other hand, increased (P < 0.05) on digestibility was observed using N from CSM or SBM. However, a better response (P <0.05) was found with N from SBM plus energy sources with milo stalk, bagasse or wheat straw supplemented with N at 1.0 or 1.5% levels.